Plasma-aided impregnation of wood with flame retardants - Pabeliña Karel G. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
Flame endurance of wood samples was increased by plasma technology as a method of impregnation. Wood samples were immersed in reactive plasmas comprised of various ratios of flame retardant solutions (bori acid, phosphoric acid r commercially-available retardants) and /or reactive gases (H2, N2). Thermal characterizations such as simultaneous thermogravimetric analysis and differential thermal analysis (TGA-DTA) and differential scanning calorimetry (DSC) were performed on the treated samples. Optimal emission spectroscopy was used to identify the plasma species present during the plasma modification. Also, the effects of plasma treatment on the surface of the wood sample in terms of surface were investigated using Fourier transform infrared (FTIR) spectroscopy.